2017
DOI: 10.1007/s10886-017-0909-x
|View full text |Cite
|
Sign up to set email alerts
|

Attraction of Three Mirid Predators to Tomato Infested by Both the Tomato Leaf Mining Moth Tuta absoluta and the Whitefly Bemisia tabaci

Abstract: Plants emit volatile compounds in response to insect herbivory, which may play multiple roles as defensive compounds and mediators of interactions with other plants, microorganisms and animals. Herbivore-induced plant volatiles (HIPVs) may act as indirect plant defenses by attracting natural enemies of the attacking herbivore. We report here the first evidence of the attraction of three Neotropical mirid predators (Macrolophus basicornis, Engytatus varians and Campyloneuropsis infumatus) toward plants emitting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 70 publications
6
48
0
3
Order By: Relevance
“…However, a preference for uninfested crop plants over clean air has also been found with Y-tube olfactometry for M. pygmaeus (Ingegno et al, 2011;Lins et al, 2014) and N. tenuis (Naselli et al, 2017;Rim et al, 2015) on tomato and eggplant (Solanum melongena L.). Similar results were found for three neotropical predatory mirids on tomato (Silva et al, 2018), by Abbas et al (2014) on tomato and D. maroccanus (today synonymized to D. bolivari according to Sánchez and Cassis, 2018), and by Pérez-Hedo and Urbaneja (2015) on sweet pepper for N. tenuis, M. pygmaeus, and D. maroccanus. Other authors have emphasized the importance of plant genotypes in explaining variability of results regarding the attractiveness of uninfested plants to natural enemies (Rapusas et al, 1996).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, a preference for uninfested crop plants over clean air has also been found with Y-tube olfactometry for M. pygmaeus (Ingegno et al, 2011;Lins et al, 2014) and N. tenuis (Naselli et al, 2017;Rim et al, 2015) on tomato and eggplant (Solanum melongena L.). Similar results were found for three neotropical predatory mirids on tomato (Silva et al, 2018), by Abbas et al (2014) on tomato and D. maroccanus (today synonymized to D. bolivari according to Sánchez and Cassis, 2018), and by Pérez-Hedo and Urbaneja (2015) on sweet pepper for N. tenuis, M. pygmaeus, and D. maroccanus. Other authors have emphasized the importance of plant genotypes in explaining variability of results regarding the attractiveness of uninfested plants to natural enemies (Rapusas et al, 1996).…”
Section: Discussionsupporting
confidence: 81%
“…Although predatory bugs have been tested for preferences among odor sources (e.g. Ingegno et al, 2011;Silva et al, 2018), it remains unknown how well these experiments reflect actual behavior in the field (Ballhorn and Kautz, 2013). In this study, we found that orientation to volatile cues does not always reflect oviposition free choice under short-distance cues, as D. bolivari showed contradictory results for tomato and calendula between the olfactometer and oviposition assays.…”
Section: Discussionmentioning
confidence: 73%
“…Besides their attraction to the GLVs (Z)-3-hexenyl acetate and (Z)-3-hexenyl propanoate, this study provided evidence that N. tenuis, M. pygmaeus, and D. bolivari are attracted to synthetic MeSA. Interestingly, previous studies showed that mirid species are attracted to whitefly-and T. absoluta-infested plants (Lins et al, 2014;Silva et al, 2018), which frequently emit these three compounds ( Angeles-L opez et al, 2012;Silva et al, 2017). Application of these compounds in the field could possibly serve to guide these predators to tomato crop areas.…”
Section: Discussionmentioning
confidence: 99%
“…These predators use various cues related to plant quality and prey availability to discriminate and select their host (Coll, 1996;Eubanks and Denno, 2000a,b;Grosman et al, 2005;Lins et al, 2014;Ingegno et al, 2016). For instance, zoophytophagous predators are attracted to volatiles from prey-infested plants (herbivore-induced plant volatiles; HIPVs) (Lins et al, 2014;De Backer et al, 2015;Silva et al, 2018). Lins et al (2014) observed that both M. pygmaeus and N. tenuis responded positively to plants infested by their prey [whitefly Bemisia tabaci Gennadius (Hemiptera: Aleyrodidae) and the tomato borer Tuta absoluta Meyrick (Lepidoptera: Gelechiidae)].…”
Section: Interactions With Host Plantsmentioning
confidence: 99%